Youth Voting Behavior in Ambon City Legislative Election - Byo, Alfian Abu Bakar; Tuanaya, Wahab; Fretes, Judy de (Journal of Government Science Studies, 2025)
The study was conducted in Nusaniwe District, Ambon City. Primary data collection involved interviews with informants who were considered knowledgeable about the voting behavior of youth in the 2019 legislative election in the area. The findings indicate that the most dominant factors influencing youth electoral choices in the 2019 legislative election in Nusaniwe District were their preference for certain candidates and psychological influences such as parental guidance, the opinions of community leaders, and peer pressure. These are classified as psychological factors according to voter behavior theory. Additionally, sociological factors, such as shared locality, and rational factors, including cost-benefit analysis and evaluation of candidates’ programs and visions, also played a role in shaping youth political choices.